Relationship between work values and intention to stay among millennials gen-Z employees: Moderating roles of employee engagement - Iman Permana; Astri Octora; Dyah Wulandari Mardyastuti; Shirley Ayu Widyaningsih (FIRM Journal of Management Studies, 2023)
This study investigates three factors in work values, namely extrinsic work values, intrinsic work values and leisure work values, and the extent of those values in influencing intention to stay on two different groups of millennials and Gen Z. This research contributes to literature by examining work values in these two generations simultaneously and its effect on their intention to stay in a company. This study also investigates the moderating role of employee engagement between work values and intention to stay. The model is empirically tested using a sample of 203 millennials and Gen Z workers in the Greater Jakarta area (Jabodetabek). We use multiple regression analysis in examining the relationship between each of these three factors on work values in influencing intention to stay. The results reveal interesting findings. Among the three values, only extrinsic work values are found to have positive significant influence on intention to stay on groups of millennials and Gen Z, while intrinsic and leisure work values do not have significant influence on intention to stay. The result does not support the moderating roles of employee engagement in strengthening the positive relationship between extrinsic work values with intention to stay. We discuss the implications of the results and the suggestion for future research.